An appraisal of tax incentives under the TIC Investment regime - Maya, Deogracious (Mzumbe University, 2024)
A dissertation submitted to the Faculty of Law in partial fulfillment of the requirements for the award of Masters Degree in Commercial Laws (LL.M. - CL) of Mzumbe University